Aligning Sustainable Development Goals into English for Journalism: A Case Study of Practical Application in ELT - Afifah Linda Sari; Radityo Tri Nugroho (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: This study explores the integration of Sustainable Development Goals (SDGs) into an English for Journalism course as a means to enrich language learning with socially meaningful content. Methodology: This research addresses that gap through a qualitative case study involving 18 undergraduate students at UIN Antasari Banjarmasin. Data were collected from teaching resources, student outputs, and reflective journals, and analyzed thematically. The research examined the design and implementation of SDG-based mind-mapping, writing broadcast news scripts on local issues, and recording news readings, aiming to connect journalistic tasks with global concerns. Findings: The findings revealed that these tasks not only improved students’ language proficiency and media literacy but also deepened their critical thinking and awareness of sustainability issues such as gender equality, clean water, and public health. Students were able to contextualize global goals through local narratives and developed confidence in using English for real-world communication. Conclusion: This study offers a replicable model for embedding socially meaningful content into English for Specific Purposes (ESP) courses, particularly in English for Journalism context, and proposes pedagogical strategies that educators can adapt in diverse contexts. Originality: While previous research has explored the theoretical potential of SDGs in fostering critical thinking and global awareness, there is limited evidence of how these goals can be applied in teaching activities. By documenting and reflecting on the teaching process and student responses, this study can enhance both language learning outcomes and student awareness of global issues.